Nanostructured Fe-N-C pyrolyzed catalyst for the H2O2 electrochemical sensing. (10th August 2021) - Candia-Onfray, Christian; Bollo, Soledad; Yáñez, Claudia; Escalona, Néstor; Marco, José F.; Menéndez, Nieves; Salazar, Ricardo; Recio, F. Javier
Abstract: Fe-N-C pyrolyzed materials have been proposed as substitutes of the noble-based catalyst for energy conversion reactions. However, their use as electrochemical sensors has not been deeply explored. In the present work, different Fe-N-C pyrolyzed catalysts were synthesized for the amperometric sensing of the H2 O2 reduction in neutral media. The catalysts were characterized by BET, TEM, FESEM, XPS, Mössbauer spectroscopy, and cyclic voltammetry. The catalysts present an N-doped graphitic matrix with a macroporous structure and mesoporous contribution. Different amounts of N-pyridinic, N-pyrrolic, N-graphitic, N-oxides, and FeN4 sites have been detected on the catalysts. Among the different active sites present in the catalysts, the FeN4 structure is proposed as the most catalytic active site for the hydrogen peroxide reduction reaction (HPRR). Under optimal conditions (0.61 V vs. NHE, 0.00 V vs. Ag/AgCl), the materials show a lineal amperometric response in the range of 0.08 and 14 µM, with a sensitivity of 31.3 µA µM −1 cm −2, and a detection and quantification limits of 0.25 µM and 0.75 µM respectively. The amperometric results indicate that the best performance is reached when increasing the amount of FeN4 active sites, and the redox potential of the FeN4 species becomes more positive. The Fe-N-C catalyst stands out for the more positive working potential than other materials proposed in the literature. Graphical Abstract: Image, graphical abstract